Ciclo de vida de painéis fotovoltaicos: recuperação do vidro como alternativa ao descarte - Tonholi, Francisnara (2021)
In order to recycle photovoltaic modules, provided by the Federal University of Technological Paraná – Campus Pato Branco/PR, researchers have investigated ways to mitigate this problem. With the expansion of the use of photovoltaic panels for energy generation, studies predict an accumulation of up to 78 million tons of waste from photovoltaic panels in 2050. Thus, in this work the module compositions and the recycling of the panel’s glass cover were studied, since the glass of a silicon solar panel accounts for about 2/3 of the device's weight. The recycling methods often require to broke the panel, which maintain the glass cover in lowvalue fragments. Here, we demonstrate that the glass can be recovered through a technical process, without being broken. Due to its chemical and mechanical resistance, this glass would be ready to be reused without the need to be melted again, bringing with it important energy savings and carbon emissions related to its production. The material would be ready to be used in another solar panel, as an architectural material or other application. In addition, we used Fourier Transform Infrared Spectroscopy (FTIRATR), Raman, Thermal Analysis, XRay Diffractometry (XRD), Optical Absorption Spectroscopy (UVVis), Scanning Electron Microscopy (SEM) and Energydispersive Xray spectroscopy (EDS) to confirm the composition of the remaining components as well as to identify aging. We confirmed that our case study panel has a composition similar to most silicon solar panels on the market, and the results indicated that it would be feasible to recover the glass in most of these devices, thus, reducing carbon emissions from the industrial photovoltaic system in more than 2 million tons per year.